2019
DOI: 10.18549/pharmpract.2019.1.1386
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy ethical practice in Jordan: assessing attitude, needs and barriers

Abstract: Background: Having a local code of ethics, based on moral obligations and virtues, known to all practicing pharmacists is important in order to guide them in relationships with patients, health professionals, and society. Objective: To investigate pharmacists’ attitude and barriers towards applying the ethical principles published by the Jordanian Pharmacists Association in the Jordanian code of ethics. Methods: The study objectives were addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…[ 42 ] This is may be because pharmacists provide useful drug information that support therapeutic decisions. Pharmacists’ have been viewed as trusted clinical information providers in UAE, [ 43 ] Iraq, [ 44 ] Jordan [ 28 ] Iran, [ 10 ] Sudan [ 45 ] and Kuwait. [ 27 ] Arguably, Egyptian pharmacists are influential sources of drug information that may affect.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] This is may be because pharmacists provide useful drug information that support therapeutic decisions. Pharmacists’ have been viewed as trusted clinical information providers in UAE, [ 43 ] Iraq, [ 44 ] Jordan [ 28 ] Iran, [ 10 ] Sudan [ 45 ] and Kuwait. [ 27 ] Arguably, Egyptian pharmacists are influential sources of drug information that may affect.…”
Section: Discussionmentioning
confidence: 99%
“…22 Ethical concern recording in this study was also quite inferior to a study in Jordan. 33 In our study, majority of the participants had reported that "lack of time" was the major barrier (85.9%) which hinder them to discuss ethical concerns with the customers followed by "lack of reliable resources" (40.0%) and "poor ethical knowledge" (37.7%). This finding is similar with other studies in Jordan, 33 Saudi Arabia 22 and Scotland.…”
Section: Discussionmentioning
confidence: 64%
“…33 In our study, majority of the participants had reported that "lack of time" was the major barrier (85.9%) which hinder them to discuss ethical concerns with the customers followed by "lack of reliable resources" (40.0%) and "poor ethical knowledge" (37.7%). This finding is similar with other studies in Jordan, 33 Saudi Arabia 22 and Scotland. 34 However, in another study conducted in Iran poor experience with ethical issues and absence of trust were reported to be major barriers against explaining ethical issues.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pharmacists nowadays carry more responsibilities and commitments to improve their practice, emphasizing on the fact that the pharmacy profession is becoming more dynamic by the day [1,2]. The role of pharmacists worldwide is expanding into a more patient-focused and outcome-oriented role compared to the previous dispensing role [1].…”
Section: Introductionmentioning
confidence: 99%